2010
DOI: 10.1037/a0015466
|View full text |Cite
|
Sign up to set email alerts
|

Global–local and trail-making tasks by monolingual and bilingual children: Beyond inhibition.

Abstract: In three experiments, a total of 151 monolingual and bilingual 6-year-olds performed similarly on measures of language and cognitive ability but bilinguals solved the global-local and trail-making tasks more rapidly than monolinguals. This bilingual advantage was found not only for the traditionally demanding conditions, incongruent global-local trials and Trails B, but also for the conditions not usually considered to be cognitively demanding, congruent global-local trials and Trails A. All the children perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
199
5
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 232 publications
(228 citation statements)
references
References 60 publications
15
199
5
9
Order By: Relevance
“…The results have been inconsistent with some researchers reporting equivalent performance for monolinguals and bilinguals (e.g., Luo, Luk, & Bialystok, 2010;Martin-Rhee & Bialystok, 2008), others reporting a monolingual advantage (e.g., Bialystok, 2010), and still others reporting a bilingual advantage (e.g., Bialystok, et al, 2008;Morales, Calvo, & Bialystok, 2013).…”
Section: Bilingual Working Memorycontrasting
confidence: 40%
See 2 more Smart Citations
“…The results have been inconsistent with some researchers reporting equivalent performance for monolinguals and bilinguals (e.g., Luo, Luk, & Bialystok, 2010;Martin-Rhee & Bialystok, 2008), others reporting a monolingual advantage (e.g., Bialystok, 2010), and still others reporting a bilingual advantage (e.g., Bialystok, et al, 2008;Morales, Calvo, & Bialystok, 2013).…”
Section: Bilingual Working Memorycontrasting
confidence: 40%
“…In most previous studies on bilingual executive function, WM span has been measured using simple span tasks, such as digit span, Corsi span, or matrix span (e.g., Bialystok, 2010;Luk, Anderson, Craik, Grady, & Bialystok, 2010;Martin-Rhee & Bialystok, 2008). The results have been inconsistent with some researchers reporting equivalent performance for monolinguals and bilinguals (e.g., Luo, Luk, & Bialystok, 2010;Martin-Rhee & Bialystok, 2008), others reporting a monolingual advantage (e.g., Bialystok, 2010), and still others reporting a bilingual advantage (e.g., Bialystok, et al, 2008;Morales, Calvo, & Bialystok, 2013).…”
Section: Bilingual Working Memorycontrasting
confidence: 38%
See 1 more Smart Citation
“…First, it offers a reinterpretation of bilinguals' better FB performance in view of current studies on the role of attentional processes in FB tasks (Rubio-Fernández 2013, 2015aRubioFernández & Geurts, 2013, 2015. Second, it puts bilinguals' better FB performance in line with recent findings on their better performance in EF tasks (Costa et al, 2008;Martin-Rhee & Bialystok, 2008;Bialystok, 2010Bialystok, , 2015Grundy & Bialystok, 2015). I will start by examining children's focus of attention in standard FB tasks, and then challenge the general assumption that passing this type of task requires inhibiting a prepotent response.…”
Section: Bilinguals Outperform Monolinguals In Fb Taskssupporting
confidence: 63%
“…More recent studies, however, have revealed that bilinguals activate information about both languages when using one language alone (for a review, see Kroll & Bialystok, 2013). Since bilingual language production requires constant monitoring of the target language in order to minimise interference from the competing language, bilinguals' EF is strengthened over time (Bialystok, 2010;. However, even so, studies of EF have not revealed a bilingual advantage that is specific to inhibitory control, or any other single component of EF (for reviews, see Hilchey & Klein, 2011;Bialystok, 2015).…”
Section: Bringing Together Bilinguals' Better Performance In Fb and Ementioning
confidence: 99%